Complications Associated With Venovenous Extracorporeal Membrane Oxygenation—What Can Go Wrong?. Issue 12 (12th September 2022) - Teijeiro-Paradis, Ricardo; Gannon, Whitney D.; Fan, Eddy
Abstract : OBJECTIVES: Despite increasing use and promising outcomes, venovenous extracorporeal membrane oxygenation (V-V ECMO) introduces the risk of a number of complications across the spectrum of ECMO care. This narrative review describes the variety of short- and long-term complications that can occur during treatment with ECMO and how patient selection and management decisions may influence the risk of these complications. DATA SOURCES: English language articles were identified in PubMed using phrases related to V-V ECMO, acute respiratory distress syndrome, severe respiratory failure, and complications. STUDY SELECTION: Original research, review articles, commentaries, and published guidelines from the Extracorporeal Life support Organization were considered. DATA EXTRACTION: Data from relevant literature were identified, reviewed, and integrated into a concise narrative review. DATA SYNTHESIS: Selecting patients for V-V ECMO exposes the patient to a number of complications. Adequate knowledge of these risks is needed to weigh them against the anticipated benefit of treatment. Timing of ECMO initiation and transfer to centers capable of providing ECMO affect patient outcomes. Choosing a configuration that insufficiently addresses the patient's physiologic deficit leads to consequences of inadequate physiologic support. Suboptimal mechanical ventilator management during ECMO may lead to worsening lung injury, delayed lung recovery, or ventilator-associated pneumonia. Premature decannulation from ECMO as lungs recover can lead to clinical worsening, and delayed decannulation can prolong exposure to complications unnecessarily. Short-term complications include bleeding, thrombosis, and hemolysis, renal and neurologic injury, concomitant infections, and technical and mechanical problems. Long-term complications reflect the physical, functional, and neurologic sequelae of critical illness. ECMO can introduce ethical and emotional challenges, particularly when bridging strategies fail. CONCLUSIONS: V-V ECMO is associated with a number of complications. ECMO selection, timing of initiation, and management decisions impact the presence and severity of these potential harms.